5% fluorouracil chemowraps in the management of widespread lower leg solar keratoses and squamous cell carcinoma. (8th May 2013) - Tallon, Ben; Turnbull, Nicholas
Abstract: Elderly patients with extensive hypertrophic solar keratoses and squamous cell carcinoma on the lower legs can pose significant management challenges. Typically these patients require surgical treatment which is complicated by comorbidities and poor background lower leg skin. 5% fluorouracil chemowraps provides a useful alternative technique for the management of diffuse hypertrophic solar keratoses and as an adjuvant, and in some situations as a palliative treatment, for squamous cell carcinomas on the lower legs.